A comprehensive review on effect of process parameters and heat treatment on tensile strength of additively manufactured Inconel-625. (2021) - Soni, Harsh; Gor, Meet; Singh Rajput, Gautam; Sahlot, Pankaj
Abstract: Additive manufacturing (AM) is a novel deposition technique to fabricate a 3D complex component. In AM, fabricating complex geometries is easy to fabricate due to layer-by-layer deposition and provides many advantages over conventional processes. AM technique is used in many industries like aerospace, automobile, marine etc. In the Selective laser melting (SLM) process, the laser is used as a heat source to fuse the material. The mechanical and microstructural properties of SLM samples are good due to high cooling rate. The Inconel 625 superalloy has superior properties in strength, good fatigue, and high creep resistance. Inconel is known for a high-temperature application in the field of aerospace and automobile. Tensile strength is one of the important factors to evaluate the quality of the build part. This comprehensive review focuses on ultimate tensile strength, elongation, yield strength, process parameter and heat treatment conditions. The effect of process parameters such as laser power, scanning speed and orientation on tensile strength is covered. It also includes effect of different heat treatment such as solution annealing, direct aging, thermal exposure and solution treatment on tensile strength, yield strength and elongation. This study would be helpful to optimum process parameters and post-processing techniques for improving tensile strength.